Connecting - Christy I. Wenger; Monica Mische; Kristina Fennelly; Laurence Musgrove; Lindsey Allgood (Journal of the Assembly for Expanded Perspectives on Learning, 2019)
Finding Meaning in our Work and Writing, Christy I. Wenger Response from Beyond, Monica Mische Reflecting on Arguing and Listening in Digital Spaces, Kristina Fennelly Sunday Morning Before Midterms, Laurence Musgrove Honoring Impulse, Attending to Gesture, Lindsey All-good